1979
DOI: 10.1128/aem.38.4.642-643.1979
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for more than one division of bacteria within airborne particles

Abstract: When the protocol that we had used to demonstrate a single division of bacterial cells in airborne particles was changed to one that increased the glycerol content of the atomizer fluid from 1 to 5% (vol/vol), thus producing larger particles, more than two (and nearly three) divisions of bacteria occurred within 6 h of aerosol time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Does the atmosphere provide a niche for particular microorganisms? (Dimmick et al, 1979;Sattler et al, 2001;Amato et al, 2007) -Does the degradation of organic compounds by bacteria play a significant role in the chemistry of liquid particles in the atmosphere? (Herlihy et al, 1987;Ariya et al, 2002;Amato et al, 2007) The answer to each of these questions either depends on or enhances our knowledge of atmospheric bacterial concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Does the atmosphere provide a niche for particular microorganisms? (Dimmick et al, 1979;Sattler et al, 2001;Amato et al, 2007) -Does the degradation of organic compounds by bacteria play a significant role in the chemistry of liquid particles in the atmosphere? (Herlihy et al, 1987;Ariya et al, 2002;Amato et al, 2007) The answer to each of these questions either depends on or enhances our knowledge of atmospheric bacterial concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several new samplers have become commercially available, namely, the glass cyclone (Fig. 6; The Glassblowers, Inc., Turnersville, NJ [7, 73]) with flow controller (Poddymeter, Ltd., Kingston‐upon‐Thames, UK), direct collector for SEM investigations (California Measurements, Inc., Sierra Madre, CA), and the MicroBio air sampler (F.W. Parrett Ltd., UK).…”
Section: Experimentation With Airborne Bacteriamentioning
confidence: 99%
“…The bacteria discussed here are those observed by the classical cultural methods. Some culturable airborne bacteria have been shown capable of reproducing while airborne [7].…”
Section: Introductionmentioning
confidence: 99%
“…Living microorganisms have been collected in the stratosphere (Imshenetsky et al, 1978), and there are several reports supporting the idea that microorganisms can live and reproduce on airborne particles (Dimmick et al, 1979). It has also been shown that microorganisms can actively grow and reproduce at temperatures near or below 0 • C in cloud droplets collected at high altitudes (Sattler et al, 2001).…”
Section: Introductionmentioning
confidence: 95%